Richard Wagner’s Der fliegende Holländer – A Flying Hebridean in Disguise? - Ahlander, Per G.L. (Scottish Studies, 2013)
Several scholars have drawn attention both to the many Scottish references in Richard Wagner’s initial sketches of The Flying Dutchman and to the close links between the opera and the composer’s own disastrous Nordic sea journey, but discussions tend to centre on the opera’s libretto. What appear to be musical reminiscences of Hebridean songs in the opera’s core thematic material have not been alluded to since Marjory Kennedy-Fraser pointed them out at the beginning of the twentieth century. Having a long-standing interest in Wagner’s oeuvre, she associated various themes and tunes she had collected in the Outer Hebrides with the German composer, and among her extant field recordings – now at Edinburgh University Library – there are indeed snippets of music that closely resemble Wagnerian leitmotifs and airs, in particular Senta’s ballad in Der fliegende Holländer. Drawing on a paper Kennedy-Fraser read to the Musical Association in London in 1918, various scattered references, and letters from Sir Granville Bantock and John Lorne Campbell, my article discusses the potential links between Hebridean songs and, in particular, Senta’s ballad.